2011
DOI: 10.4172/2167-1079.1000104
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Treatment Failure Among Tuberculosis Patients on Directly Observed Theraphy in Rural Primary Health Care Centres in Ogun State, Nigeria

Abstract: Introduction: Poor compliance with treatment (default) is thus a major impediment to effective tuberculosis (TB) chemotherapy worldwide even though free medication may be available, many patients may not be successfully treated. This study was designed to identify risk factors associated with treatment failure during TB treatment within the National Tuberculosis and Leprosy Control Programme [NTBLCP programme] in rural primary health care centres in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This result is consistent with the results of studies cunducted in china and Uganda, [73], [74] which revealed a significant association between positive mycobacterium test result and treatment failure. Another study conducted in Nigeria [75] showed no significant difference in treatment failure between the smear positive and smear negative test results. The findings of this study can be attributed to presence of atypical mycobacterium bacilli that are not sensitive to the first line treatment of TB treatment 2(RHZE) 4(RH) [76] Second line treatment starts in already advanced bacillary load.…”
Section: Discussionmentioning
confidence: 91%
“…This result is consistent with the results of studies cunducted in china and Uganda, [73], [74] which revealed a significant association between positive mycobacterium test result and treatment failure. Another study conducted in Nigeria [75] showed no significant difference in treatment failure between the smear positive and smear negative test results. The findings of this study can be attributed to presence of atypical mycobacterium bacilli that are not sensitive to the first line treatment of TB treatment 2(RHZE) 4(RH) [76] Second line treatment starts in already advanced bacillary load.…”
Section: Discussionmentioning
confidence: 91%